EDUKASI PENDAMPINGAN RELAKSASI OTOT PROGRESIF DAN 5 PILAR TERHADAP PERUBAHAN PENGETAHUAN DAN KESTABILAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS TIPE 2 - Susanti, Susanti; Fajriyah, Novita; Kristiani, Rina Budi; Yobel, Sosilo; Bistara, Difran Nobel (Community Development in Health Journal, 2024)
Introduction & Aim: An unhealthy lifestyle and inactivity are the main causes of type 2 diabetes mellitus (T2DM), which disrupts the body's ability to metabolize glucose into energy. This community service project aims to assess type 2 diabetes patients' blood glucose levels and level of knowledge regarding Progressive Muscle Relaxation and the Five Pillars of education. Method of Activity: A 5-Pillars teaching program and progressive muscle relaxation were given to 25 type 2 diabetes patients who had previously visited the Bulak Community Health Center. This six-week community service project involved multiple stages of action, including an initial survey, education, application, assistance, and assessment, and it was conducted at Jalan Bulak Setro RT 02 RW 04 Bulak Surabaya. Community conduct is assessed based on knowledge and blood sugar levels. To assess the efficacy of the service, data were examined statistically using the Wilcoxon signed rank test. Results: The community behavior that this service can alter is demonstrated by the 100% increase in knowledge (p = 0.000) and the normal blood glucose levels of 64% of respondents (p = 0.004). Disscusion: For individuals with type 2 diabetes mellitus, progressive muscle relaxation education and the 5-pillars of diabetes mellitus therapy yield the best outcomes in terms of preventing complications like diabetic neuropathy. An extensive strategy to raise sufferers' awareness is to offer information and support so that individuals with DMT2 can adopt a healthier lifestyle in the hopes that their blood glucose levels will return to normal.